Antioxidant Activity and Immunomodulatory Effect of Stachytarpheta sp. Leaf Extract on Phagocytic Activity of Mice Peritoneal Macrophages in Alloxan Induction - Iffa Afiqa Khairani; Wahyuni Dian Lestari; Elisa Nurma Riana; Jeane Siswitasari Mulyana; Hida Arliani Nur Anisa; Rizka Fatriani; Silvia Andriani (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
Hyperglycemia is a condition characterized by elevated blood glucose levels, which is a hallmark of diabetes mellitus. Prolonged hyperglycemia not only disrupts glucose homeostasis but also impairs the immune response. The condition of hyperglycemia in the body can increase free radicals and oxidative stress, thus can impair various macrophage functions, including their ability to engulf and eliminate pathogens. The bioactive constituents in Stachytarpheta sp. may contribute to reducing oxidative damage and enhancing immune system function. This study aims to evaluate both the antioxidant capacity and the immunomodulatory effects of Stachytarpheta sp. leaf extract on the phagocytic activity of peritoneal macrophages in alloxan-induced diabetic mice. Alloxan is widely used in research to induce hyperglycemia (diabetic conditions) in experimental animals. The antioxidant activity of the extract was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay, while phagocytic activity of peritoneal macrophages was performed in vivo using male mice. Stachytarpheta sp. leaf extract from Beteng Sari Village, East Lampung has very strong antioxidant activity against DPPH with IC50 value 14,85 ± 0,30 μg/mL. This extract at doses of 200, 300, and 400 mg/kgBW can be an immunomodulator that maintains the phagocytic activity of macrophage cells in alloxan-induced mice.